Quantification of intrathoracic fat adds prognostic value in women undergoing myocardial perfusion imaging. (1st October 2019) - Haider, Ahmed; Possner, Mathias; Messerli, Michael; Bengs, Susan; Osto, Elena; Maredziak, Monika; Portmann, Angela; Fiechter, Michael; Giannopoulos, Andreas A.; Treyer, Valerie; Gaisl, Thomas; von Felten, Elia; et al.
Abstract: Aim: Amongst patients with coronary artery disease (CAD), women experience relatively worse outcomes as compared to men. Evidence to date has failed to explore unique female imaging targets as major determinants of cardiovascular risk. We sought to assess the prognostic value of epicardial (EFV) and intrathoracic fat volume (IFV) quantification in women and men with suspected and known CAD. Methods and results: Intrathoracic fat volume and EFV were calculated from non-contrast CT and analyzed in a propensity-matched cohort of 190 patients (95 women, mean age 62.5 ± 11.3 years) undergoing myocardial perfusion imaging (MPI) and coronary computed tomography angiography (CCTA) for evaluation of CAD. IFV and EFV were significantly lower in women as compared to men (198.2 ± 78.4 vs 293.2 ± 114.7 cm 3 and 105.6 ± 48.9 vs 135.8 ± 60.9 cm 3, p < 0.001) and showed a strong association with coronary artery calcium score (CACS) and obstructive CAD in women (p < 0.05), but not in men. Fat volumes were not related to abnormal MPI in either population (p = NS). During a median follow-up of 2.8 years, high IFV was associated with reduced event free survival (log rank = 0.019 vs low IFV) in women, but not in men. Accordingly, a multivariate Cox regression model adjusted for cardiovascular risk factors, CACS, CCTA, and MPI findings selected IFV as a significant predictor of major adverse cardiovascular events (MACE) in women (HR 1.32, 95%CI 1.18–1.55, p = 0.001). Conclusion: Quantification of IFV provides incremental prognostic value for MACE in women, beyond that provided by traditional risk factors and imaging findings. Highlights: IFV provides incremental prognostic value for MACE in women. IFV values are significantly higher in women who experience adverse outcome. EFV and IFV are associated with CACS and obstructive CAD in women and men.